2004
DOI: 10.1042/cs20030387
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial stiffening and thickening in the paretic lower limb in patients with hemiparesis

Abstract: Atherosclerosis has two key components, thickening and stiffening of arterial wall. These parameters are quantified ultrasonographically by IMT (intima-media thickness) and PWV (pulse wave velocity). In the present study, we determined the FA IMT (IMT of the bilateral femoral artery) and PWV of femoral-ankle (PWV fa) and brachial-ankle (PWV ba) segments in order to examine whether the degree of atherosclerosis is different between paretic and non-paretic lower limbs in 24 patients with hemiparesis. The values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Not only aortic PWV but also baPWV has been shown to be a good independent predictor for the presence of coronary artery disease in men (11,12). Thus far, we have reported the significance of baPWV in patients with hemiparesis (13). Although subclinical hypothyroidism is a major risk factor for atherosclerosis, few studies have been performed on arterial stiffening using baPWV measurements in subclinical hypothyroid patients.…”
Section: H Ypothyroidism Is Increasingly Recognized Asmentioning
confidence: 97%
See 1 more Smart Citation
“…Not only aortic PWV but also baPWV has been shown to be a good independent predictor for the presence of coronary artery disease in men (11,12). Thus far, we have reported the significance of baPWV in patients with hemiparesis (13). Although subclinical hypothyroidism is a major risk factor for atherosclerosis, few studies have been performed on arterial stiffening using baPWV measurements in subclinical hypothyroid patients.…”
Section: H Ypothyroidism Is Increasingly Recognized Asmentioning
confidence: 97%
“…An automatic waveform analyzer (model BP-203RPE; Colin Co., Komaki, Japan) was used to measure PWV simultaneously with blood pressure, electrocardiogram, and heart sounds, as we and others have previously described (10,13). Briefly, subjects were examined in the supine position after 5 min of bed rest, with electrocardiogram electrodes placed on both wrists, a microphone for detecting heart sounds placed on the left edge of the sternum, and cuffs wrapped around the brachium and ankles.…”
Section: Pwvmentioning
confidence: 99%
“…We have shown that abdominal aortic calcification is significantly associated with all-cause mortality in maintenance hemodialysis patients (Okuno et al, 2007). Reduced bone mineral density (BMD) has been linked to increased arterial thickness and stiffness based on increased intima-media thickness (Yamada et al, 2005) and pulse wave velocity in Japanese subjects (Tanaka et al, 2006;Okabe et al, 2004). Furthermore, we have shown that the rate of reduction of BMD is an independent predictor of all-cause mortality in male hemodialysis patients and that the presence of vertebral fracture predicts mortality in female hemodialysis patients .…”
Section: Introductionmentioning
confidence: 98%
“…Clinically overt and subclinical hypothyroidism is associated with a high rate of chronic kidney disease (CKD) (1,2,3,4,5,6,7) and is an established cardiovascular risk factor (1). Subclinical hypothyroidism occurs in 5-15% of the general population and is highly prevalent in women over 60 years of age (1,2).…”
Section: Introductionmentioning
confidence: 99%